2021
DOI: 10.21831/jsd.v10i2.43043
|View full text |Cite
|
Sign up to set email alerts
|

Sintesis dan Karakterisasi Nanopartikel Magnetit (Fe3O4) Berbasis Pasir Besi Pantai Glagah Kulon Progo dengan Metode Kopresipitasi pada Berbagai Variasi Konsentrasi NH4OH

Abstract: Sintesis dan karakterisasi nanopartikel magnetit (Fe3O4) yang berbasis pasir besi Pantai Glagah, Kulon Progo telah berhasil dilakukan. Sintesis magnetit (Fe3O4) dilakukan dengan metode kopresipitasi pada berbagai variasi konsentrasi larutan pengendap NH4OH (10%, 15%, 20%, dan 25%).  Karakterisasi XRD, SEM EDS, dan VSM dilakukan untuk mengetahui pengaruh variasi konsentrasi larutan pengendap NH4OH terhadap struktur mikro dan sifat kemagnetan bahan magnetit (Fe3O4). Berdasarkan hasil XRD, variasi konsentrasi la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
0
0
1
Order By: Relevance
“…Beberapa penelitian telah berhasil mensintesis Fe3O4 dengan pasir besi sebagai bahan utamanya [9,10]. Pada tahun 2019, Prasetyowati [11] telah berhasil melakukan sintesis Fe3O4 dari pasir besi Pantai Glagah Kulonprogo menggunakan metode kopresipitasi.…”
Section: Pendahuluanunclassified
“…Beberapa penelitian telah berhasil mensintesis Fe3O4 dengan pasir besi sebagai bahan utamanya [9,10]. Pada tahun 2019, Prasetyowati [11] telah berhasil melakukan sintesis Fe3O4 dari pasir besi Pantai Glagah Kulonprogo menggunakan metode kopresipitasi.…”
Section: Pendahuluanunclassified
“…Another study by Prasetrowati et al synthesized Fe3O4 with varying concentrations of NH4OH. VSM testing results showed that sample 2 (15% NH4OH) had a saturation magnetization (Ms) of 25.7 emu/g, remanent magnetization (Mr) of 0.06 emu/g, and coercivity (Hc) of 0.023 T. In contrast, sample 4 (25% NH4OH) had a saturation magnetization (Ms) of 23.6 emu/g, remanent magnetization (Mr) of 2.02 emu/g, and coercivity (Hc) of 0.019 T. Both samples were classified as soft magnetic materials [9].…”
Section: Introductionmentioning
confidence: 99%
“…The coprecipitation method is the simplest, most economical, and most efficient way to obtain Fe3O4 powder from natural iron sand. The particles produced by this method are relatively stable and highly insoluble in solvents [9], [10], [11] Iron sand contains iron particles like magnetite found along rivers and beaches. These deposits are formed through the processes of weathering, erosion by surface water, and wave action that breaks down the parent rock.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several methods for producing Fe3O4 nanoparticles exist, including sol-gel [7], hydrothermal [8], coprecipitation [9], and sonochemistry [10,11]. The coprecipitation method is one effective method of producing Fe3O4 nanoparticles.…”
Section: Introductionmentioning
confidence: 99%